The digital divide in the US criminal justice system. (February 2022) - Ramirez, Fanny
The growing use of digital evidence from smartphones and social media has led to a digital divide in the US criminal justice system that advantages law enforcement and prosecutors while further increasing the vulnerability of poor people and people of color who rely on public legal assistance. Drawing on a year-long ethnographic study of one of the first digital forensics laboratories in a public defender office, I argue that digital inclusion in the form of better resources for public defenders is necessary for equitable and fair representation in today's criminal justice system. Findings show that access to digital forensic technologies is an important equalizing tool that allows public defenders to (1) mount strong, data-driven cases; (2) create counter narratives that challenge depictions of marginalized defendants as dangerous; and (3) engage in nuanced storytelling to highlight the complexities of human relationships and life circumstances that shape cases.